2021
DOI: 10.2217/bmm-2020-0422
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Inflammatory Biomarkers in Patients with Covid-19 Infections: Bahrain Experience

Abstract: Aim: COVID-19 pandemic continues and dearth of information remains considering the utility of various inflammatory biomarkers. We carried out the present study to delineate the roles of these biomarkers in various strata of patients with coronavirus infection. Materials & methods: A retrospective study was carried out after obtaining approval from the relevant Ethics Committee. Patients established with COVID-19 infection as shown by positive real-time quantitative PCR test were included. Details on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Farid et al investigated the use of inflammatory biomarkers in diagnosis of the severity of COVID-19 disease and found that an increase in several biomarkers such as D-dimer, serum ferritin, and CRP was related to severe forms of COVID-19 infection. Moreover, Farid et al revealed that the serum level of IL-6 in patients who suffered from a severe form of COVID-19 disease was very high [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farid et al investigated the use of inflammatory biomarkers in diagnosis of the severity of COVID-19 disease and found that an increase in several biomarkers such as D-dimer, serum ferritin, and CRP was related to severe forms of COVID-19 infection. Moreover, Farid et al revealed that the serum level of IL-6 in patients who suffered from a severe form of COVID-19 disease was very high [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory findings have revealed that damage to immune effector cells and exacerbation of pro-inflammatory cytokines to COVID-19 infection may lead to lung damage, thus contributing to the growing death rate [ 1 , 6 ]. Moreover, it has become clear that the lymphocyte and platelet counts in COVID-19 patients hospitalized in Intensive Care Units (ICU) decrease severely, while the neutrophil count in their blood increases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory markers and indices including the biochemical, coagulation and hematologic parameters have been associated with dysregulated inflammatory cascade in COVID-19 [6][7][8]. These inflammatory markers/indices have been shown to aid clinical diagnosis and monitoring of COVID-19 patients in several reports [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory markers and indices including the biochemical, coagulation and hematologic parameters have been associated with dysregulated inflammatory cascade in COVID-19 [6][7][8]. These inflammatory markers/indices have been shown to aid clinical diagnosis and monitoring of COVID-19 patients in several reports [6][7][8][9][10][11][12][13]. However, most of these markers have been evaluated predominantly among the Caucasian populations and very few have evaluated the predictive potentials of these markers in severe COVID-19 infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…There was a correlation between serum levels of IL-6 and ferritin (r = 0.64, p = 0.0001) [48]. Chen at el.…”
Section: Discussionmentioning
confidence: 92%